Design and Development for Smart Home via IoT Technology: A Work in Progress - Mohamed Ariff, M.I. (IEEE Computer Society, 2021)
The smart home concept is an emerging innovation that helps home automation. Smart home development and adoption is still a new phenomenon relatively limited in Malaysia. The implementation of smart home concept makes it easier for homeowners to monitor their homes from anywhere and anytime via the Internet of Things (IoT) principle. However, the implementation of smart home may expose homeowners to network security, information privacy, and other physical safety issues. Therefore, this paper is a work in progress on the design and development of a smart home IOT-based project. As a proof of concept, this project focuses on the design and development of a smart auto gate system. The proposed smart auto gate system is designed to be controlled by a mobile application via a wireless connection. This project aims to develop a minimal priced, and extensible wireless smart home auto gate system using IoT which then employs the combination of mobile application, and a cloud server. Thus, it will allow home users to control the automatic gate through a user-friendly mobile application interface. Â© 2021 IEEE.